2020
DOI: 10.1002/rnc.5262
|View full text |Cite
|
Sign up to set email alerts
|

Robust trajectory tracking control of a marine surface vessel using asymmetric error constraints and output feedback

Abstract: This article investigates the problem of robust trajectory tracking for a marine surface vessel in the presence of asymmetrical error time-varying constraints and output feedback. To deal with system uncertainties, adaptive neural networks (NNs) are used to approximate unknown dynamics model parameters and external disturbances. To obtain unmeasured velocities, a predictive observer based on output feedback is developed to estimate unknown velocities. A tan-type asymmetric barrier Lyapunov function is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In [22], the BLF-based control method is proposed for robotic systems with fullstate constraints, which demonstrated that the BLF design method has advantages in dealing with state constraint problems of the El system. For research position constraint problems, a BLF-based controller is proposed for the marine vessel with uncertainty in [23], which also demonstrates the superiority of BLF in the El system design. e BLF technique can dynamically constrain the error within the specified range and guaranteed the performance of tracking control, which enhances the robustness of the control.…”
Section: Introductionmentioning
confidence: 83%
“…In [22], the BLF-based control method is proposed for robotic systems with fullstate constraints, which demonstrated that the BLF design method has advantages in dealing with state constraint problems of the El system. For research position constraint problems, a BLF-based controller is proposed for the marine vessel with uncertainty in [23], which also demonstrates the superiority of BLF in the El system design. e BLF technique can dynamically constrain the error within the specified range and guaranteed the performance of tracking control, which enhances the robustness of the control.…”
Section: Introductionmentioning
confidence: 83%
“…Consider the dynamic system (5) where the functions a(𝜘, t), b(𝜘, t) satisfy Assumptions 1 and 2 for unknown parameters 𝛿 1 , 𝛿 2 , 𝛾 1 ∈ R + . Then, for any initial conditions 𝜘(0), 𝜎(0), there exist a finite-time 0 < T F and a parameter 𝜖 ∈ R + , so that a real 2-sliding mode, that is, |𝜎| ≤ 𝜂 1 and | σ| ≤ 𝜂 2 , is established ∀t ≥ T F , in presence of bounded additive (9) and multiplicative (6) perturbations with unknown boundaries, via the AST control…”
Section: Preliminariesmentioning
confidence: 99%
“…For fully‐actuated vessels, trajectory tracking has been widely studied. Different techniques have been applied, such as data‐driven control, 3,4 neural‐network‐based control, 5,6 and extended state observer‐based control 7 . Nevertheless, given the theoretical and practical challenge it represents, the trajectory tracking scenario is still a research interest for underactuated USVs 2,8 …”
Section: Introductionmentioning
confidence: 99%
“…where Remark 2 Assumption 2 shows that the disturbance is bounded without any requirements on the smoothness and hence includes those of [5,11,12,14,17,21,27] where the disturbance must be continuously differentiable. Actually, the disturbance may be quite unexpected in practice, such as non-smooth or even noncontinuous, which can not be overcome by the compensation technique in the literature.…”
Section: Problem Formulationmentioning
confidence: 99%